Perception and Self Awareness among Preservice Educators Teaching Multiculturalism - Rolle, Dorinda (CIEX JOURNAL, 2017)
Globalism has caused multicultural education to develop into an increasingly significant educational component. It has become imperative for educators to be proficient in facilitating the learning of this concept to their students. While teachers have an important role in helping students embrace diversity, their own perceptions, attitudes, and self-awareness about the subject may pose a major challenge to the overall purpose of multicultural education.